PENDEKATAN HUMANISTIK GURU DALAM MENDORONG PARTISIPASI SISWA PADA PEMBELAJARAN MAHARAH KALAM - Mufidatur Ramadhani; Fina Aunul Kafi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Learning maharah kalām (Arabic speaking skills) is not solely related to the mastery of linguistic aspects but is also influenced by affective dimensions that shape students’ willingness to participate in oral communication. In classroom practice, language anxiety and fear of making mistakes often become major barriers, causing students to hesitate to speak despite having understood the material. This condition highlights the importance of pedagogical approaches that foster a psychologically safe and supportive learning environment. This study aims to analyze how a humanistic approach implemented by teachers contributes to enhancing students’ participation in maharah kalām learning. This study employed a qualitative approach with a case study design focusing on Arabic language learning at the senior Islamic high school level. Data were collected through in-depth interviews, classroom observations, and document analysis. The data were analyzed thematically through a coding process to identify patterns and meanings derived from participants’ experiences. The findings reveal that psychological safety, dialogic interaction between teachers and students, and well-structured classroom management are key factors in encouraging students to take linguistic risks and actively engage in oral communication. Student participation is influenced not only by instructional methods but also by the quality of pedagogical relationships established during the learning process. This study underscores the significance of a humanistic approach in Arabic language learning and contributes to strengthening the role of affective and relational dimensions in enhancing students’ communicative participation. ABSTRAKPembelajaran maharah kalām dalam bahasa Arab tidak hanya berkaitan dengan penguasaan aspek linguistik, tetapi juga dipengaruhi oleh dimensi afektif yang menentukan keberanian siswa dalam berpartisipasi secara lisan. Dalam praktik pembelajaran di madrasah, kecemasan berbahasa dan kekhawatiran melakukan kesalahan sering menjadi hambatan yang menyebabkan siswa enggan berbicara, meskipun telah memahami materi. Kondisi ini menunjukkan pentingnya pendekatan pedagogis yang mampu menciptakan lingkungan belajar yang aman secara psikologis dan relasional. Penelitian ini bertujuan untuk menganalisis kontribusi pendekatan humanistik yang diterapkan guru dalam mendorong partisipasi siswa pada pembelajaran maharah kalām. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus pada pembelajaran Bahasa Arab di tingkat madrasah aliyah. Data dikumpulkan melalui wawancara mendalam, observasi kelas, dan analisis dokumen pembelajaran. Analisis data dilakukan secara tematik melalui proses pengkodean untuk mengidentifikasi pola makna dari pengalaman partisipan. Hasil penelitian menunjukkan bahwa rasa aman psikologis, interaksi dialogis antara guru dan siswa, serta pengelolaan kelas yang terstruktur menjadi faktor utama dalam meningkatkan keberanian siswa untuk berpartisipasi. Partisipasi siswa tidak hanya dipengaruhi oleh metode pembelajaran, tetapi juga oleh kualitas relasi pedagogis yang dibangun dalam proses pembelajaran. Penelitian ini menegaskan pentingnya pendekatan humanistik dalam pembelajaran bahasa Arab serta memberikan kontribusi pada penguatan dimensi afektif dan relasional sebagai faktor kunci dalam meningkatkan partisipasi komunikatif siswa.